Arthroscopic and Endoscopic Spinal Surgery Text and Atlas - Kambin, Parviz; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2005)
Minimally invasive spinal surgery has progressed significantly from the first blind nucleotomy in the 1970s to such advanced techniques as endoscopic fragmenectomy, decompression of lateral recess stenosis, foraminoplasty, and spinal stabilization. In Arthroscopic and Endoscopic Spinal Surgery: Text and Atlas, an authoritative panel of surgeons, researchers, inventors, experts, and the creator of the field describe and illustrate various techniques and approaches that are currently used for the treatment of painful spine pathologies. The authors guide the surgeon and demonstrate step-by-step how minimally invasive techniques can be used for the treatment of spinal disorders without violating the content of the spinal canal and how anatomical structures appear through an endoscope. They also provide visual aid for the diagnosis and recognition of various anatomical structures of the spine and cutting-edge methods that prevent the development of postsurgical failed-back syndrome. Up-to-date and instructive, Arthroscopic and Endoscopic Spinal Surgery: Text and Atlas will teach surgeons how minimally invasive techniques can be used for the treatment of spinal disorders without violating the content of the spinal canal and normal anatomy.
History of Surgical Management of Herniated Lumbar Discs From Cauterization to Arthroscopic and Endoscopic Spinal Surgery -- Arthroscopic and Endoscopic Anatomy of the Lumbar Spine -- Instruments and Surgical Approaches for Minimally Invasive Spinal Surgery Via Posterolateral Access -- Herniated Lumbar Disc and Lumbar Radiculopathy -- Management of Discogenic Pain and Spinal Instability Using Minimally Invasive Surgical Techniques -- Lateral Recess Stenosis of Lumbar Spine Foraminoplasty -- Role of Epidural and Radicular Veins in Chronic Back Pain and Radiculopathy -- Diagnostic and Therapeutic Percutaneous Transpedicular Approaches to the Spine -- Selective Endoscopic Discectomy -- Minimally Invasive Posterior Fusion and Internal Fixation With the Atavi® System -- Vertebral Augmentation for Osteoporotic Compression Fractures -- Principles of Transthoracic, Transperitoneal, and Retroperitoneal Endoscopic Techniques in the Thoracic and Lumbar Spine -- Use of Laser in Minimally Invasive Spinal Surgery and Pain Management -- Minimally Invasive Techniques in Pain Management -- Experience With Minimally Invasive Nucleus Replacement -- Interspinous Process Implant for Treatment of Lateral and Central Spinal Stenosis -- Frameless Stereotactic Imaging Techniques in Minimally Invasive Spinal Surgery -- The Rise and Fall of Chemonucleolysis -- Lumbar Microendoscopic Discectomy.
Keywords: Medicine; Neurosurgery; Orthopedics; Medicine & Public Health; Orthopedics; Neurosurgery; Electronic books